Implementation of Cold Chain System in Central Region of Thailand - Pornphunkul, Summana; Pongchit, Panjal (Journal of Health Science of Thailand, 1995)
The study of the implementation of cold chain system was carried out in 11 provinces in the Central Region of Thailand. Studied samples were a group of 203 health personnel working in the Expanded Programme on Immunization (EPI). Questionnaires concerning personal characteristics, supporting factors and the management of cold chain system were sent to and collected from the respondants by mail. It was found that quality of cold chain implemented was associated with respondents' characteristics (sex, age, years of work in EPI and economic status) at p<0.01. The result of this study suggested that the implementation of cold chain system in the provinces of the Central Region should be reorganized both in logistics supplies and method of cold chain in order to increase the skill and knowledge of the personnel in charge.